Banana, Gingers and Papaya Cell Cultures for High Throughput Agriculture - Khalid, Norzulaani; Chee, W.W.; Bokhari, F.; Kiat, T.S.; Idris, F.D.; Mohamad, M.; Ibrahim, H.; Annuar, S.; Othman, R.Y.; Rahman, N.A. (Malaysian Society for Molecular Biology and Biotechnology, 2010)
There is considerable interest in developing plant cell cultures that could facilitate rapid propagation of elite materials and for the production of phytochemicals. In Malaysia, there is an urgent need for sufficient supply to meet the voluminous demand for seedlings which are important plantation and cash crops. Considering the cost of labour and infrastructure in conventional plantation, propagation in liquid culture is a practical way to produce clonal propagules at a low cost. Plant cell cultures could also provide an alternative source of phytochemicals. These cultures will ensure continuous high quality compounds and will also prevent the extinction of the valuable plants in their natural habitat. Alternatively, bioreactor could be used to maintain plant cell cultures on a large scale to enable the production of high quality cell lines of the major cash crops at a significant volume. One of the advantages of growing cell cultures in bioreactors is the opportunity to control critical parameters in order to reduce variations which could affect product quality and process reproducibility. Besides being able to produce high-quality planting materials, plant cell cultures also allow genetic manipulation for trait improvement through either genetic engineering or mutagenesis (mutation breeding). Metabolomics is another possible endeavour in an attempt to enhance the production of certain fine chemicals in plants. This is to resolve the perpetual problem of non viable harvest of phytochemicals for commercialisation especially for the use of drug and product development. In this paper, we will discuss the development of embryogenic cell suspensions of banana, papaya, and selected gingers (Boesenbergia rotunda, Zingiber zerumbet and Curcuma xanthorhiza) which have been field tested. The banana and papaya cell suspensions could produce up to 15, 000 plants and 7, 000 plants respectively for every 1 ml of settled cell volume within 5 -6 months. For the papaya and gingers, chromatographic spectrums of the phytochemical extracts from the cultivated type explants, tissue culture derived materials and cell suspension will be compared. The presence of the compounds in cell suspension will allow us to adopt genetic engineering technologies either to up-regulate or down-regulate certain enzymes for the enhancement of the targeted compounds in plants. In addition, physical parameters could be used to help increase the phytochemicals. For transgenic technologies, early flowering gene, Soc 1, has been successfully introduced into banana suspension but without the expected physiological changes when plants were transplanted.